Social determinants of health: time for action - Gboyega A Ogunbanjo (South African Family Practice)
By the time, you receive this issue of the journal, the joint 5th WONCA Africa and 20th South African Academy of Family Physicians conference would have ended in Pretoria South Africa on 20 August 2017. The theme of the joint conference forms the basis of this editorial. So what is “Social Determinants of Health (SDH)”? The World Health Organization (WHO) defines it as the conditions in which people are born, grow, live, work and age. These circumstances are shaped by the distribution of money, power and resources at global, national and local levels. The SDH are mostly responsible for health inequities – the unfair and avoidable differences in health status seen within and between countries. It is acknowledged that “health equity and social determinants” are critical components of the post-2015 sustainable development goals (SDG) global agenda and of the push towards progressive achievement of universal health coverage (UHC). If we have to reduce health inequities, the approach will be to address both SDH and UHC in an integrated and systematic manner.1